Working like dogs : the service dog guidebook - Davis, Marcie, 1965-; Bunnell, Melissa, 1968- (Crawford, CO : Alpine Publications, 2007)
Working Like Dogs: The Service Dog Guidebook is the resource book for service dogs that captures personal stories, checklists and practical tips to provide the reader with an A-Z guide about service dogs. It is a must read for anyone who is considering a service dog, has a service dog, is raising or is responsible for the care of a service dog, and dog lovers alike who want to connect with the power of the human-animal service dog partnership. This book is the ideal addition to every service dog training program as the resource for puppyraisers, service dog applicants and recipients.
Includes bibliographical references and index.
Keywords: Service dogs